Legal instruments, policy tools: a look at the impact of the judgments of the Inter- American Court of Human Rights in Latin American constitutions - Bregagio Lazarte, Renata (2014)
The current research tries to recognize how the Inter-American Court of Human Rightscan influence in the legal and constitutional reforms in Latin American countries. It tries to understand what elements are required for those reforms to happen. It is stated that it requires human rights movements with knowledge of the Inter-American system and a favorable State context of at least one branch of the State. Finally, it was found that, in the cases studied, thecontext determines whether what the Inter-American Court says is applied or not.